RESHAPING INVESTMENTS AMIDST 2020 PANDEMIC: A PROSPECT THEORY WAY - et. al., Poornima Tapas (International Journal of Modern Agriculture, 2021)
The unprecedented breakdown of COVID-19 pandemic has brought to core the colossal of transitions in the business and economy. Overall the Indian economy has witnessed loss of human lives and turmoil leading crisis situation and slow growth rate. Indian economy is diverse, the challenges and the contraction of growth region- wise is not same. The intensity of business closures, job cuts and unemployment has displaced the financial sector. Retail investments were greatly affected due to changing investor preferences. The paper attempts to analyse the burden of COVID-19 on the savings decisions of retail segment of investors for insurance products and gold. The research encompasses a comprehensive review of the articles published in secondary sources for understanding the trends in the insurance sector and in gold investments. The paper relates to apply the prospect theory to the changing uncertain investment environment. Several experiences of the retail investors have been ascertained based on the observations for 6 months from January to June 2020 time period. The findings indicate investor biases towards other asset classes to reduce risk and shift towards insurance products and online gold products. Theoretically, the paper contributes to the field of pandemic research and behavioural economics in terms of risk aversion in unprecedented times. Pandemic leaves a long-lasting impact on the economy; such instances time test the theories which serve as enablers for identifying the best practices in addressing uncertainty.